Psychosocial Intervention in the Social Rehabilitation of Child Victims of Violence Who Have Run Away: A Case Study at the Medan City Social Protection Home (UPT) - Jevania J; Husni Thamrin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the psychosocial dynamics and the effectiveness of social work interventions for child victims of violence who have run away from home. The method used is a qualitative approach with an explanatory case study design. Primary data collection was conducted through in-depth interviews, participatory observation, genograms, and eco-maps. The intervention integrated the Trauma-Informed Care (TIC) approach, individual counseling using art therapy techniques, peer support group activities, and the mobilization of formal and informal support systems, which were then analyzed to draw conclusions based on the existing issues. The results showed a significant improvement in emotional regulation, a reduction in acute anxiety symptoms and hypervigilance, the elimination of maladaptive coping behaviors, and the restoration of clients’ interpersonal relationship capacity. However, family reintegration could not be achieved during the internship period due to chronic dysfunction within the nuclear family microsystem.